Expression of Regeneration-Associated Proteins in Primary Sensory Neurons and Regenerating Axons After Nerve Injury-An Overview - Dubový, Petr; Klusáková, Ilona; Hradilová-Svíženská, Ivana; Joukal, Marek (The anatomical record, 2018)
Peripheral nerve injury results in profound alterations of the affected neurons resulting from the interplay between intrinsic and extrinsic molecular events. Restarting the neuronal regenerative program is an important prerequisite for functional recovery of the injured peripheral nerve. The primary sensory neurons with their cell bodies in the dorsal root ganglia provide a useful in vivo and in vitro model for studying the mechanisms that regulate intrinsic neuronal regeneration capacity following axotomy. These studies frequently need to indicate the regenerative status of the corresponding neurons. We summarize the critical issues regarding immunohistochemical detection of several regeneration-associated proteins as markers for the initiation of the regeneration program in rat primary sensory neurons and indicators of axon regeneration in the peripheral nerves. This overview also includes our own results of GAP43 and SCG10 expression in different DRG neurons following double immunostaining with molecular markers of neuronal subpopulations (NF200, CGRP, and IB4) as well as transcription factors (ATF3 and activated STAT3) following unilateral sciatic nerve injury. Anat Rec, 301:1618-1627, 2018. © 2018 Wiley Periodicals, Inc.
Keywords: transportní proteiny; membránové proteiny; Sensory Receptor Cells; spinální ganglia; Cornified Envelope Proline-Rich Proteins; Membrane Proteins; Nerve Regeneration; Carrier Proteins; zvířata; Animals; axony; Ganglia, Spinal; Biomarkers; Microtubule Proteins; protein GAP-43; GAP-43 Protein; mikrotubulární proteiny; Axons; nervové receptory; biologické markery; regenerace nervu; Stress, Physiological; korneocytární obal - proteiny bohaté na prolin; fyziologický stres